In Depth Analysis of the Leading Causes of Maternal Mortality Due to Cesarean Section in Iran - Nasrin Changizi; Golnaz Rezaeizadeh; Leila Janani; Mamak Shariat; Abbas Habibelahi (Tehran University of Medical Sciences, 2017)
Objective: Despite the declining trend of maternal mortality (MMR) in Iran between 1990 and 2013, direct causes are still the major reasons for maternal death. One of these direct causes is complications of cesarean section (CS). Since the rate of CS in Iran is quite high (47.9%) and the trend continues to rise, there is an alarming threat of the possibility of increasing MMR in the country as a result of cesarean section complications, especially in repeated cases. In this study, we attempted to determine the indications of CS in reported maternal mortality, with special attention to risk factors predisposing to CS and/or to maternal mortality. Materials and methods: A retrospective study was implemented for the period between March 2009 and March 2012. All nationally reported data regarding maternal death during pregnancy, labor and 42 days after parturition during these 3 years was collected and input to software specially designed for this project. Subsequently, cases of maternal death related to pregnancy termination by cesarean section were selected for analysis. Results: There were 393 cases of maternal death with cesarean section as the termination method. Indications of CS were mostly emergency and repeat and the leading causes of death were postpartum hemorrhage and hypertensive disorders. Most of these deaths occurred in academic hospitals and the most common type of delay was brought about by hospital management, specifically personnel issues. Conclusion: Based on this study, acknowledging CS as a serious health threat endangering every achievement in the maternal health program is the most important policy and efforts should be focused on provision of guidelines for realistic CS indications, standardized CS procedures, and post CS care as well as propagation of training courses in risk management and high risk case-finding protocols.